Efficacy of Topical 1% Oxiconazole Cream in the Treatment of Dermatophytosis (Journal of Enam Medical College, 2014)
Background: Dermatophytosis is a geographically widespread group of fungal infections. Tinea corporis and tinea cruris are the most common dermatophytoses in Bangladesh. Oxiconazole has recently been introduced in Bangladesh in the treatment of dermatophytoses. Objective: To evaluate the efficacy of topical 1% oxiconazole cream once daily in the treatment of tinea corporis and tinea cruris. Materials and Methods: A clinical trial was carried out in the department of Dermatology and Venereology, Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet on 81 patients with tinea corporis and/or tinea cruris. The patients were instructed to apply 1% oxiconazole cream once daily for 2 weeks with clinical assessment made at weekly intervals during treatment period. Results: The mean age of the patients was 32.5 ± 10.5 years, with tinea corporis in 47 (58.0%) patients and tinea cruris in 34 (42.0%). The mean clinical assessment score declined from 6.6 ± 1.3 at baseline to 3.9 ± 1.2 at week 1, 0.9 ± 1.3 at week 2 and 0.7 ± 1.1 at week 4. Reduction of clinical assessment score from baseline to end of the treatment period was statistically significant (p